Export Credits : Developments and Prospects 1986. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1986)
This paper discusses developments and issues concerning export credits from the perspective of the economic adjustment process of indebted developing countries. This emphasis is consistent with the principle that officially supported export credit-whether it takes the form of direct official credits or insurance and guarantees on privately funded credits-is an instrument of commercial financing for exports and not a means of aid finance. All creditor governments have a broad range of objectives in using the economic instruments at their disposal to help overcome the adjustment problems of heavily indebted countries, with which important bilateral trade relations are being maintained. In support of an expansion in world trade and notwithstanding the competitive element, export credit insurance and guarantees may have a special role in helping to catalyze private credit flows, especially since such a role coincides with the interest of private lenders to shift away from general purpose balance of payments finance to trade and project finance.